Step-by-step explanation:
I'm learn this too hahaha
Hello!
To find the y-intercept of any given equation, you will need to substitute x for zero.
Also, to write the y-intercept as an ordered pair, it will look like (0, y), where y is the y-intercept, and x-value is zero because we substituted zero into all the x-values of the equation.
y = -(2^x) (substitute x = 0)
y = -(2^0) (any exponent raised to the power of zero is equal to one)
y = -(1) (simplify)
y = -1
Therefore, the y-intercept of the function y, is (0, -1).
Answer:
13
Step-by-step explanation:
hope this helped!
Answer:
D) 11 cause it is only found form multiplying 1 and 11